An exploration of the 2016 violent protests in Vuwani, Limpopo Province of South Africa - Shai, K.B.; Nkuna, V. M (Main India, 2018)
In the recent past, South Africa have witnessed a wave of community protests which have been attributed to a number of factors. Limpopo Province of South Africa also had a fair share of violent protests in several areas. However, protests in other areas except Vuwani have received limited media coverage, which in turn resulted in scant scholarly attention. This is to say that the community protests in Vuwani and the surrounding areas have dominated the public discourse due to the scale of violence that they produced. Despite this, the causes of the 2016 community protests in Vuwani have not been uniformly understood and this unfortunate development resulted in disastrous interventions by different stakeholders including the government. Based on qualitative research, this de-colonial paper argues that the recent community protests in Vuwani can be well-understood when located within a historical perspective.
Article published in the Main India 98 (3-4) : 425-436
Keywords: Vuwani; Coloniality; Community protests; Violence; Tribalism; Demonstrations--South Africa